2018
DOI: 10.1016/j.pharep.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Insulin deprivation decreases insulin degrading enzyme levels in primary cultured cortical neurons and in the cerebral cortex of rats with streptozotocin-induced diabetes

Abstract: Our data suggest that insulin deprivation, rather than high glucose, is a significant determinant of IDE regulation. As evidence indicates potential roles for IDE in diabetes and AD, understanding the mechanisms regulating IDE expression may be important in developing new treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Hyperglycaemia induced by STZ leads to progressive insulin resistance of the peripheral tissues, which results in mice being unresponsive to insulin [41]. Also, it has been reported that diabetes induced by STZ decreases IDE levels in the brains of rats [42]. Villa-Pérez et.al reported that liver-specific ablation of IDE leads to hepatic insulin resistance and glucose intolerance without affecting insulin clearance in mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia induced by STZ leads to progressive insulin resistance of the peripheral tissues, which results in mice being unresponsive to insulin [41]. Also, it has been reported that diabetes induced by STZ decreases IDE levels in the brains of rats [42]. Villa-Pérez et.al reported that liver-specific ablation of IDE leads to hepatic insulin resistance and glucose intolerance without affecting insulin clearance in mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…There are data indicating that liver-specific ablation of insulindegrading enzyme causes hepatic insulin resistance and glucose intolerance (Villa-Perez et al 2018) and that pancreatic β-cell-specific deletion of insulindegrading enzyme leads to dysregulated insulin secretion (Fernandez-Diaz et al 2019). Furthermore, insulin deprivation in rats with streptozotocininduced diabetes down-regulates insulin degrading enzyme level in the cerebral cortex (Kazkayasi et al 2018). There are also data indicating that ablation of amyloid precursor protein (APP) increases insulindegrading enzyme levels and activity in brain and other tissues, which clearly demonstrate a novel role for APP as an upstream regulator of IDE in vivo and represents a new molecular link connecting APP to metabolic homeostasis (Kulas et al 2019).…”
mentioning
confidence: 99%
“…However, the affinity of insulin for IDE is greater than Aβ, which means that insulin and Aβ will compete with each other for IDE. As a result, the occurrence of hyperinsulinemia may result in the accumulation of Aβ (Kazkayasi et al, 2018). Our results showed that the IDE expression of the hippocampus or cortex of HFD/STZ-induced T2DM rats was greater than the other groups, not only in line FIGURE 5 | Protein levels of PSD-95 in the hippocampus (A) and cortex (B), and BDNF levels in the hippocampus (C) and cortex (D) in high-fat diet and streptozotocin-induced type 2 diabetic rats treated with alpha-lipoic acid for 13 weeks.…”
Section: Discussionmentioning
confidence: 99%